Injuries and Occupational Diseases That Occur to Physiotherapists - Eiman Elhanesh (AlQalam Journal of Medical and Applied Sciences, 2025)
Physical therapy practice exposes therapists to various musculoskeletal injuries, which passively affect their daily life. Given the nature of physical therapy practice, this occupation leads to more injury incidents that may affect the musculoskeletal system, circulatory system, and nervous system. This study aimed to identify the most common occupational diseases that occur to physical therapists in Al-Zawiya city, and their impact on demographic factors (gender, age, educational level, years of experience). A cross-sectional study was designed with a self-administered questionnaire. Forty-eight participants were recruited from different physical-therapy clinics in Al Zawiyah city, Libya. Data were analyzed by SPSS V27 version. The study revealed that 100% of participants were affected by occupational injury, (89.6%) females, (10.4%) males, (72.9%) Less than 30" age group, (87.5%) holds a Bachelor's degree, (47.9%) have practical service experience up to 5 years. This study exhibited (68.8%) are suffering from back pain, (64.6%) experienced shoulder and hand pain associated with neck pain, (60.4%) muscle strain and fatigue, (33.3%) leg pain associated with back pain (sciatica), (27.1%) knee pain, (20.8%) carpal tunnel syndrome, (12.5%) varicose veins, (8.3%) Calculus spur (corn) and (6.3%) elbow pain. A chi-square statistic (10.50) and p-value (0.033) indicate a statistically significant association between years of experience >5 years and the prospect of experiencing muscle strain and fatigue. In addition, there is a significant association between age and muscle strain and fatigue with chi-square statistic (11.111) and p-value (0.004). The most common occupational diseases that affect physical therapists are clearly stated in this study as muscle strain and fatigue, back pain, shoulder pain, and hand pain. Years of experience and age have an impact on injury occurring.